ANALISIS KELAYAKAN USAHA TANI CABAI(Capsicum annum L.) RAMAH LINGKUNGAN DI KABUPATEN HULU SUNGAI SELATAN PROVINSI KALIMANTAN SELATAN - Wilna Yuliani; Bambang Joko Priatmadi; Emmy Sri Mahreda; Hilda Susanti (Universitas Lambung Mangkurat, 2021)
Chili farmers in Hulu Sungai Selatan Regency experience several obstacles in carrying out environmentally friendly chili farming, besides that there is no research that analyzes the financial feasibility of the farming business. This study aims to identify the problems of farmers in environmentally friendly chili farming from the aspects of cultivation, production and environmental techniques compared to conventional farming, and analyze the feasibility of environmentally friendly chili farming. This research is a survey research. Determination of the location and sample of the study was carried out purposively in Padang Batung District which is an environmentally friendly chili farming area in Hulu Sungai Selatan Regency. Respondents' data was collected using the census method. Identification of problems using descriptive analysis method. The analysis used is the calculation of profit (π) and business feasibility. The results showed that the problems faced by environmentally friendly chili farmers in the aspect of cultivation techniques were slower land preparation; need a process in the manufacture of fertilizer media and vegetable pesticides; the reaction of plant fertilizers and pesticides on plants is rather slow; and spraying of botanical pesticides should be done regularly. The profit of environmentally friendly chili farming is Rp. in Hulu Sungai Selatan Regency it is feasible to operate based on the results of the Net Benefit Cost Ratio analysis of 107.37, Net Present Value of 92,684,379, Internal Rate Return of 10.637% and Return On Investment of 336%.